Nonlinear Control based on Feedback Linearization for Double- Electromagnet Suspension System - Maghsoudlou, A.; Barzamini, R.; Farahani, K. D. (Elektronika ir Elektrotechnika, 2011)
In this paper a feedback linearization control for double electromagnet suspension system is presented that addresses the coupling effects between two groups of electromagnetic trains. The controller has been developed based on feedback linearization and some reasonable assumptions of nonlinear mathematical rules. The proposed method in tracking has a satisfying performance in presence of unknown changes in the mass. It also shows robustness against the presence of measurement noises because sensors in plant collect noise from the environment. The simulation results show the capability of the proposed algorithm in the presence of input and output perturbation. Ill. 13, bibl. 7 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.151